Bioaccumulation of Heavy Metals in Anuran Tadpoles: A Study in Barak Valley, Assam - Pammi Singh (International Journal of Aquatic Biology, 2016)
Heavy metal pollution plays an important role in global biodiversity decline. However, there is paucity of information concerning the effects of metals on amphibians. In the present study, investigations were made on the accumulation of heavy metals, copper (Cu) and lead (Pb) in water, sediment and tadpoles inhabiting the water bodies of Barak Valley, Assam. Tadpoles of six different anuran species, Hoplobatrachus tigerinus, Leptobrachium smithi, Clinotarsus alticola, Fejarvarya sp., Sylvirana leptoglossa and Euphlyctis cyanophlyctis were selected for this purpose. Heavy metal concentrations were determined in intestine, liver and tail of tadpole samples of these species. The results revealed that the copper concentration in water samples was within the maximum permissible limit of WHO (2 mg L-1), but the concentration of lead in water samples increased beyond the permissible limit of WHO (0.01 mg L-1) resulting in possibilities of higher accumulation of the metal in tadpoles and decline of amphibians’ population. Total concentration of Cu in the tadpoles of different species of amphibians followed the order: H. tigerinus > S. leptoglossa > E. cyanophlyctis > C. alticola > Fejarvarya sp. > L. smithi, while concentration of lead followed the order: E. cyanophlyctis > C. alticola > S. leptoglossa > Fejarvarya sp.> H. tigerinus > L. smithi.